Extracellular vesicle-mediated intercellular and interorgan crosstalk of pancreatic islet in health and diabetes - Wei, Junlun; Wang, Zhenghao; Han, Tingrui; Chen, Jiaoting; Ou, Yiran; Wei, Lan; Zhu, Xinyue; Wang, Ke; Yan, Zhe; Han, Yuan-Ping; Zheng, Xiaofeng (Frontiers in Endocrinology, 2023)
Diabetes mellitus (DM) is a systemic metabolic disease with high mortality and morbidity. Extracellular vesicles (EVs) have emerged as a novel class of signaling molecules, biomarkers and therapeutic agents. EVs-mediated intercellular and interorgan crosstalk of pancreatic islets plays a crucial role in the regulation of insulin secretion of β-cells and insulin action in peripheral insulin target tissues, maintaining glucose homeostasis under physiological conditions, and it’s also involved in pathological changes including autoimmune response, insulin resistance and β-cell failure associated with DM. In addition, EVs may serve as biomarkers and therapeutic agents that respectively reflect the status and improve function and viability of pancreatic islets. In this review, we provide an overview of EVs, discuss EVs-mediated intercellular and interorgan crosstalk of pancreatic islet under physiological and diabetic conditions, and summarize the emerging applications of EVs in the diagnosis and treatment of DM. A better understanding of EVs-mediated intercellular and interorgan communication of pancreatic islets will broaden and enrich our knowledge of physiological homeostasis maintenance as well as the development, diagnosis and treatment of DM.